EARLY DETECTION OF BREAST CANCER AT PUBLIC HEALTH CENTER IN REJOSO, NGANJUK - Gondo Mastutik; Sjahjenny Mustokoweni (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
The objective was to convey knowledge about procedures for early detection of breast cancer and screening of breast cancer as an effort to reduce the number of cases of advanced breast cancer. The activity was held at the Public Health Center in Rejoso, Nganjuk and was attended by 71 participants. The participants' understanding was measured by a questionnaire containing questions about breast cancer risk factors and knowledge about breast cancer. Questionnaires were given as pre-test and post-test. After attending the lecture presentation, there was an increase in understanding of 11%. Participants in this activity based on the risk factors of not having children and x-ray radiation, all of them do not have a risk of developing breast cancer. Furthermore, based on data on breastfeeding less than 6 months, aged more than 25 years, had a tumor in the breast, and had a family suffering from breast cancer, the participants in this activity had a risk of breast cancer that were 16.67%, 88.1%, 7.14%, and 14.29% respectively.This activity can increase public understanding of procedures for early detection of breast cancer so that people can carry out breast self-examinations at home every month. In this activity, participants can perform breast examinations by medical personnel so that they can help the community to carry out free breast examinations at community health centers.